Analysis of Land Surface Temperature Changes in East Lombok Regency Using the Cloud-Based Platform Google Earth Engine - Dani, Ifan Hasnan; Hardi, Rida Alkausar; Al Paqih, Muhammad Imam; Ulfa, Kurnia; Robbaniyyah, Nuzla Af'idatur; Alfian, Muhammad Rijal (Universitas Airlangga, 2025)
This study uses Google Earth Engine, a cloud computing platform, to examine variations in land surface temperature in East Lombok Regency between 2010 and 2020. This study uses MODIS satellite data and is analyzed using Google Earth Engine by adapting a mathematical method—namely, the Random Forest Algorithm from discrete mathematics. According to the results, the temperature increased from its lowest point in 2010 (14.32°C) to its maximum point in 2020 (36.19°C), rising to 16.67°C and 37.74°C. Due to residential growth, Wanasaba, Pringgabaya, and Sambelia saw the biggest increases. Comprehensive temperature monitoring is made possible by Google Earth Engine, which facilitates the effective processing of large-scale spatial data. These results offer a scientific foundation for policy decisions and are essential for environmental management and climate change mitigation. In addition to supporting environmental monitoring initiatives, this study provides a reference for related studies in other areas dealing with issues related to land use and climate change. This research is important for the Central Lombok government as a basis for mitigation efforts in responding to temperature changes and their implications for land use change.